PENYULUHAN DAMPAK NARKOTIKA DAN OBAT TERLARANG KEPADA MASYARAKAT DESA LUMBAN PEA TIMUR, KABUPATEN TOBA - Surjadi Rimbun; Agustina Veronika; Mawar G. Tarigan; Batara Simangunsong; Marlina Rajagukguk; Budi D. Sembiring; Edwin A. Pakpahan; Harry Butar-butar; Irene R. T. Damanik; Nasib M. Situmorang; Thomas Silangit; Donald F. Sitompul; Renatha N. H. Nainggolan; Sanggam B. Hutagalung; Titus Imanuel; Nur Azizah Ainun (Universitas Methodist Indonesia, 2022)
Community Service (PkM) is carried out by the Faculty of Medicine Universitas Methodist Indonesia by providing counselling the effect of Narcotics and Drug abuse. PkM was held on 8-11 June 2022 at Lumban Pea Timur, Balige,Toba District, North Sumatera. The method used is to provide counselling/lectures and provide motivation, then followed by question and answer to obtain results and solutions as a form of solving problems and obstacles faced. The results of PkM with counselling are very effective considering that there are still many people who do not get information about Narcotics and Drug abuse. With this counselling, the public becomes aware of the Narcotics and Drugs abuse problem. Thus, it is hoped that the people of Lumban Pea Timur will aware and know how to prevent their community from Narcotics and drug abuse.